PENERAPAN REGRESI COX UNTUK MENGANALISIS VARIABEL YANG BERPENGARUH TERHADAP DURASI STUDI MAHASISWA - Wulandari, Dewi; Widyastuti, Rhoudhotul; Prasetyowati, Dina (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2024)
One aspect that concerns stakeholders in a university is the study duration of students because this is one of the determinants of the quality of a university. In the Mathematics Education study program, at Universitas PGRI Semarang, there has never been any research on the length of study of students. So we conducted this study to determine the factors that significantly influence students' study duration. We applied Cox regression to data on students of the Mathematics Education study program at Universitas PGRI Semarang from entering 2017 until graduating in various years from 2021 to 2023 with predictor variables of Cumulative Achievement Index, gender, parental educational background, and student’s participation in the organizations. These data were collected using a questionnaire and data triangulation was confirmed through interviews. Meanwhile, the students’ study duration data is the secondary data that has been documented in the information system of Universitas PGRI Semarang. Analysis using Cox Regression is very suitable for the case study in this study because the dependent variable in this study is survival data. In addition, Cox Regression is known as a method that is relatively easy, simple and does not require survival data to have a certain distribution. From the analysis results, it was found that the Cumulative Achievement Index is the factor that has the most significant influence on the length of student study.